Internal standardization of LA-ICP-MS immuno imaging via printing of universal metal spiked inks onto tissue sections. Issue 3 (22nd December 2015) - Hoesl, Simone; Neumann, Boris; Techritz, Sandra; Sauter, Guido; Simon, Ronald; Schlüter, Hartmut; W. Linscheid, Michael; Theuring, Franz; Jakubowski, Norbert; Mueller, Larissa
Abstract : This paper presents the application of printed metal spiked inks for standardization of tissue sections analyzed by LA-ICP-MS imaging. Abstract : Formalin-fixed paraffin-embedded (FFPE) specimen from biopsy materials are a widespread sample format for pathologists and medical researchers. Pathologists are archiving vast numbers of FFPE samples which can be stored for decades. Conventional immunohistochemical staining (IHC) of biomarkers on FFPE tissue sections is one of the most important analytical techniques for cancer diagnosis and pathology in general. However standardization for IHC samples and quality management is tedious and differs significantly from clinic to clinic. Combining established IHC staining strategies with modern mass spectrometry mediated methods would increase it's potential and enable access of large FFPE archives for multiplexed quantitation purposes. In this work element mass spectrometry and a new ink-jet printed internal standardization approach was successfully combined with IHC staining to facilitate quantitative multiplex assays for archived FFPE samples. The printing strategy improves elemental image resolution and reproducibility of paraffin embedded breast cancer tissue sections in laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) using conventional IHC staining as a model system to investigate the new capabilities of this technique. For the internal standardization we applied a conventional CD-ink-jet printer to print a metal spiked ink onto the top of thin layer tissue sections with constant density. Printing was carried out in a direct comparison to an iodination of the tissue section as previously described as an alternative standardization method. The use of the printed internal standard allowed correction of the fluctuation during the laser ablation process and compensated instrumental drift effects. Mediated by the ink correction approach we achieved better signal-to-background-ratios (SBR) of 74 and better spatial resolution of 30 μm compared to iodination (SBR = 23). This improved performance was demonstrated on tumorous areas in FFPE breast cancer tissue sections and allowing detection of Her-2 in tumorous areas of this tissue with significantly improved contrast.